[Rezension von: D'Antonio, William V., 1926-, Religion, politics, and polarization] - Wilson, J. Matthew (A journal of church and state, 2015)
In modern research on religion and politics, much attention has been given to the relationship between religious convictions and issue preferences in the mass public. There has been considerably less focus on the connection between personal faith and political action among governmental elites. William D'Antonio, Steven Tuch, and Josiah Baker's volume seeks to fill this gap, providing a systematic and thorough analysis of the changing religious composition of the U.S. Congress over the last fifty years, the increase in partisan polarization over that same time period, and the relationship between these two phenomena. While not all of their conclusions are equally compelling, their study is a valuable contribution to the limited literature on religion and Congress, and merits attention from anyone interested in how the much-discussed “culture wars” have played out in Washington's corridors of power ...